Exploring cutting structure in film, with applications to the films of D. W. Griffith, Mack Sennett, and Charlie Chaplin. (27th August 2015) - Baxter, Mike; Khitrova, Daria; Tsivian, Yuri
Abstract: Two graphical methods of exploring aspects of cutting structure in film using shot-length data are presented. The first of these converts the cumulative frequencies of shot-lengths to tabular form that can be displayed in various ways, including the use of correspondence analysis. The method is used to investigate the differences in cutting rates used by Mack Sennett and Charlie Chaplin while directing films for the Keystone Company in 1912–14. Results suggest that previous analyses based on the average shot-length may over-simplify the contrast, and some evidence for the evolution of Sennett's style in 1913 is also suggested. The methods used, like much of the literature, do not take into account the time-series structure of the shot-lengths. In the second approach presented, this is allowed for by smoothing the time-series of shot-lengths using non-parametric regression. A computer-intensive way of presenting results graphically is developed, that does not commit the analyst to a particular choice of smoothing level, and is used to investigate an 'hypothesis' about D. W. Griffith's cutting style suggested by a 'prescription' for pacing implied in comments made in an article published under his name in the 1920s. It is shown that his major feature films between 1914 and 1921 conform to the prescription, but there is not much evidence for it in his earlier and later work.